Penguatan Pembelajaran Moral Anak melalui Dolanan Sepak Bola dan Engklek: Analisis Diagnostik sebagai Dasar Pengembangan Tindakan Pedagogis - Suhendro, Eko; Andika Alvin Pratama; Adifa kurniawan Harjito putra (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
Purpose – This study aims to analyze children’s moral learning in traditional football and engklek games as a diagnostic basis for developing pedagogical actions. The study responds to the need to transform spontaneous play experiences into reflective moral learning, particularly in relation to fairness, rule compliance, empathy, negotiation, and moral agency. Design/methods – This study employed a qualitative observational approach with a pedagogical diagnostic design. Data were collected through ethnographic observation, field notes, moral episode tracking, simple interviews, and post-observation coding. The participants were children aged 9–10 years who played football and engklek in a community setting in Karang Talun, Wukirsari, Imogiri, Bantul. The data were analyzed thematically through data condensation, coding, categorization, and interpretation. Data credibility was strengthened through source triangulation, technique triangulation, and cross-checking between observation notes and interview data. Findings – The findings show that traditional football and engklek games naturally provide social spaces for children’s moral learning. In football, children demonstrated fairness through team division, rule enforcement, peer correction, and compromise in resolving disputes about boundaries and valid goals. In engklek, moral dynamics emerged through turn-taking, helping peers understand rules, debating minor violations, and resolving conflict by restarting turns. However, the diagnostic findings also indicate several pedagogical problems, including inconsistent rule compliance, pragmatic compromise, situational empathy, and unequal moral agency among children. Based on these findings, this study proposes pedagogical actions involving rule co-construction, role rotation, guided moral reflection, peer mediation, and empathy-based questioning after play. The novelty of this study lies in positioning traditional games not merely as cultural play activities, but as diagnostic spaces for designing moral learning actions. Keyword: Moral Learning, Traditional Games, Football, Engklek, Pedagogical Action, Children